PERCEPTION OF EUROPEAN TOURIST TOWARD BALI AS TOURISM DESTINATION - I Gusti Bagus Rai Utama (Jurnal Manajemen dan Kewirausahaan, 2018)
This research aimed to determine main attractor factors of Bali tourism and predominantly factors that determine the European travel to Bali. It was designed by using research survey that involving 167 European tourist selected purposively. Confirmatory factor analysis techniques were used to analyse a wide range of variables Balinese charm. The results showed the main attractor factors of Bali tourism are (1) Immigration, security of destination, and travel agencies, (2) The prices, the accommodation, food and transportation, (3) The history, culture, and natural beauty. While the most dominant factor in determining European tourists travelled to Bali were immigration, security of destination, and travel agencies. The findings also indicated that the images of Bali tourism are the destination's history, culture, and nature. These three variables were in accordance with expectations of European tourists who have been known as travellers who like the interested on history, culture, and the beauty of the scenery.